Job Satisfaction of Service Quality Moderator on Employee Performance of the Investment Office and One-Stop Integrated Service of Padang Panjang City - Syamsul Akmal (Journal of Economics and Social Sciences (JESS), 2026)
This study is motivated by the inconsistency of employee performance despite the relatively good public service quality at the Investment and One-Stop Integrated Service Office (DPMPTSP) of Padang Panjang City. Service quality serves as a key indicator in licensing and administrative services; however, it does not fully reflect consistent individual performance. This study aims to analyze the effect of service quality on employee performance and examine the role of job satisfaction as a moderating variable. This research employs a quantitative approach with a causal design and is analyzed using Structural Equation Modeling-Partial Least Squares (SEM-PLS). The population consists of all employees of DPMPTSP Padang Panjang City, with a census technique involving 33 respondents. Data were collected through Likert-scale questionnaires and analyzed using SmartPLS 4. The results indicate that service quality has a positive and significant effect on employee performance, with a path coefficient of 0.662 and p-value < 0.05. However, job satisfaction does not have a significant effect on employee performance and does not moderate the relationship between service quality and employee performance. These findings suggest that employee performance is more influenced by organizational structural factors, such as regulations, service standards, and work systems, than by individual psychological factors. The study implies that improving service quality is the primary strategy to enhance employee performance, while job satisfaction remains important as a supporting factor in maintaining motivation and productivity.